Analisis Pengaruh Input Terhadap Nilai Produksi dan Pendapatan Pengrajin Kulit di Kota Denpasar - Dwipayanti, Kadek Fitri; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
This research is aiming to analyze the availability effect of material, capital, labor and  production value against income,and also to analyze the use of production value in mediation the effect of availability of materials, capital , labor against the income of leather craftmanship in Denpasar.Data gathering methods are observation,interview,and deep interview.The analyzing data technique that we used is path analysis and sobel testing to analyze indirect effect through mediation variable.The result of the research show materials that always available hasn't effecting the production value. Capital and labor give positive and significant effect against the production value. Availability of materials, capital and production value give positive and significant effect against the income,but the labor didn't give positive effect against the income.Production value is the mediation variable of the effect of the materials availablity,capital,and the labor of leather craftmanship in Denpasar.
Keywords: Ketersediaan bahan baku; Modal; Tenaga Kerja; Nilai Produksi; Pendapatan